A review of HRM practices and labor productivity: Evidence from libyan oil companies - Mohamed M.I.; Mutalib M.A.; Abdulaziz A.M.; Ibrahim M.; Habtoor N.A.N. (Canadian Center of Science and Education, 2024)
Indexed by Scopus